Peningkatan Ranah Kognitif Melalui Metode Schaffolding Pada Pembelajaran Pendidikan Agama Islam - Mira, Mira; Takdir, Takdir; Fitriani, Fitriani; P, Sudirman (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study aims to determine the increase in the cognitive domain of students through the scaffolding method in PAI learning in Class XI OTP 4 at SMKN 1 Sinjai. This study used the type of PTK research, the subjects in this study were 25 students in class XI OTP 4 and the researcher as the executor of the applied method and the teacher as the observer. The type of action applied is that there are two cycles, where each cycle consists of 4 stages, namely planning, action, observation, and reflection. Used were observation, tests, and documentation. Analysis technique is using validity test, reliability test, descriptive statistical observation, and N-Gain analysis. The results showed that in the first cycle of action, the average score of students was 0.4304 in the low category. While in the action cycle 2 obtained as much as 0.7443 with the high category. Therefore, it can be concluded that the application of the scaffolding method can improve the cognitive domain of students in PAI learning in Class XI OTP at SMKN 1 Sinjai.